Profesor Tadeusz Krwawicz - Kapusta, Maria; Lenkiewicz, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The work introduces the contemporary generation of ophthalmologists to a profile of prof. Tadeusz Krwawicz, one of the most outstanding worldwide authorities on ophthalmology. It presents the professional and scientific achievements which the Professor had during his activity as the Head of the Chair Ophthalmology and the Ophthalmologic Clinic of the Medical University of Lublin. Furthermore, the reader’s attention is drawn to the Professor’s interests in painting and hunting.